Efficient Sulfur Host Based on Yolk‐Shell Iron Oxide/Sulfide‐Carbon Nanospindles for Lithium‐Sulfur Batteries. Issue 5 (2nd February 2021) - Xie, Dongjiu; Mei, Shilin; Xu, Yaolin; Quan, Ting; Härk, Eneli; Kochovski, Zdravko; Lu, Yan
Abstract: Numerous nanostructured materials have been reported as efficient sulfur hosts to suppress the problematic "shuttling" of lithium polysulfides (LiPSs) in lithium‐sulfur (Li−S) batteries. However, direct comparison of these materials in their efficiency of suppressing LiPSs shuttling is challenging, owing to the structural and morphological differences between individual materials. This study introduces a simple route to synthesize a series of sulfur host materials with the same yolk‐shell nanospindle morphology but tunable compositions (Fe3 O4, FeS, or FeS2 ), which allows for a systematic investigation into the specific effect of chemical composition on the electrochemical performances of Li−S batteries. Among them, the S/FeS2 −C electrode exhibits the best performance and delivers an initial capacity of 877.6 mAh g −1 at 0.5 C with a retention ratio of 86.7 % after 350 cycles. This approach can also be extended to the optimization of materials for other functionalities and applications. Abstract : The great yolk‐shell spindle : Fe3 O4 −C, FeS−C, and FeS2 −C are synthesized with a yolk‐shell nanospindle morphology and their electrochemical performance in lithium‐sulfur batteries is systematically studied. The S/FeS2 −C cathode exhibits better long‐term cycling stability than the S/FeS−C cathode. Moreover, FeS2 nanoparticles kinetically facilitate lithium polysulfide (LiPS) conversion reactions.